2021
DOI: 10.1038/s41598-021-98212-4
|View full text |Cite
|
Sign up to set email alerts
|

Designs for a two-dimensional Si quantum dot array with spin qubit addressability

Abstract: Electron spins in Si are an attractive platform for quantum computation, backed with their scalability and fast, high-fidelity quantum logic gates. Despite the importance of two-dimensional integration with efficient connectivity between qubits for medium- to large-scale quantum computation, however, a practical device design that guarantees qubit addressability is yet to be seen. Here, we propose a practical 3 × 3 quantum dot device design and a larger-scale design as a longer-term target. The design goal is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As far as the physical realization of qubits is concerned spin is envisioned as the promising candidate [32]. Spin-a fundamental property like charge or mass, is associated with subatomic particles like protons, electrons and neutrons.…”
Section: Spin Transfer Torque-based Quantum Computingmentioning
confidence: 99%
“…As far as the physical realization of qubits is concerned spin is envisioned as the promising candidate [32]. Spin-a fundamental property like charge or mass, is associated with subatomic particles like protons, electrons and neutrons.…”
Section: Spin Transfer Torque-based Quantum Computingmentioning
confidence: 99%
“…The ability to arrange self-assembling formation of Siquantum-dots (QDs) on SiO 2 into arbitrary arrays or patterns is crucial for applications in functional nanodevices: singleelectron (or hole) transistors, [1][2][3][4][5] quantum computations, [6][7][8][9][10][11][12][13] optoelectronics, [14][15][16][17][18] and information storages. [19][20][21][22][23][24] So far, many approaches exist to the ordered spatial arrangement of Si-based QDs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Toward large-scale integrated silicon quantum computers, methods of constructing two-dimensional QD arrays have been theoretically investigated to reduce the enormous number of wires. [12][13][14][15][16][17][18] Several experimental attempts are also underway to develop feasible two-dimensional QD arrays. [19][20][21][22][23] We previously developed two-dimensional large-scale QD arrays with CMOS circuits and demonstrated that each QD could be selectively operated within the array.…”
Section: Introductionmentioning
confidence: 99%